The Influence of PGR (Practice, Generalization, Reinforcement) Technique toward Students’ Ability to Distinguish between Gerund and Present Participle - Siti Niah; Wandy Syahfutra; Prih Febtiningsih (Faculty of Teacher Training and Education, 2019)
Abstract The objectives of the research were to investigate the influence of PGR technique toward student’s ability to distinguish between Gerund and Present Participle and to know the students’ ability to distinguish both of them. The researcher applied quasi experimental method and quasi experimental design (time series) O1, O2, O3, O4, O5, O6 to find the “t” value of the scores and percentage to calculate the data from the tests. The research was conducted at the third semester students of English Education Department Faculty of Teachers Training and Educational Science Pakuan University Bogor. The researcher choose purposive sampling to take one class from 5 (five) classes and 21 (twenty one) students as the sample. The result of the research shows that there is a positive influence of PGR technique and it is proved by the “t” table of the research 4.47 which is higher than the critical value of “t” with 0.01 level of significance (2.845) and the level of 0.05 (2.086) for two tailed test. The result of the tests also shown that the students will be easier understand the difference between gerund and present participle by PGR technique. Keywords: Grammar, Gerund, Present participle, PGR Technique.